2019
DOI: 10.24815/siele.v6i2.14103
|View full text |Cite
|
Sign up to set email alerts
|

Channeling assessments in English language learning via interactive online platforms

Abstract: Technology adoption in classrooms has impacted the way educational practitioners conduct assessments. Online quizzes are preferred compared to paper-pencil based tests. However, very few information that explains the contribution of online assessment towards holistic attainment of students in English. The present study aimed at examining the effects of online assessments on students’ performance. This research employed a quasi-experimental study to evaluate the role of interactive online assessments toward stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
2
10
0
1
Order By: Relevance
“…First, surprisingly, the majority of the students were interested in e-learning, which might be caused by several factors, including the freedom to study anywhere and anytime and cost-efficient. These e-learning benefits are similar to what Effendi and Zhuang (2005) and Yulia et al (2019) found in their studies. By using elearning, students could save time and money because they did not need to travel to classes as it could be done in any location during the students' preferred time.…”
Section: Positive Features Of E-learning Implementationsupporting
confidence: 89%
“…First, surprisingly, the majority of the students were interested in e-learning, which might be caused by several factors, including the freedom to study anywhere and anytime and cost-efficient. These e-learning benefits are similar to what Effendi and Zhuang (2005) and Yulia et al (2019) found in their studies. By using elearning, students could save time and money because they did not need to travel to classes as it could be done in any location during the students' preferred time.…”
Section: Positive Features Of E-learning Implementationsupporting
confidence: 89%
“…In this regard, we suggest that the implementing institution incorporate plagiarism checking tools to assure that the submitted tasks are of learners' own works. This is particularly challenging especially when it comes to assessing learners' tasks given through an online learning platform (Yulia, et al, 2019;Ogange et al, 2018;Vonderwell, et al, 2007). Since we did not conduct in-depth research on such a case, we may not be able to offer further data on this matter.…”
Section: Resultsmentioning
confidence: 99%
“…Through the use of technology, EFL learners get more opportunities to search authentic materials from real language use. Moreover, a study by Yulia et al (2019) found that online assessment increases students' mastery of listening skills and reading skills.…”
Section: Technology In Teaching English As Second/foreign Language Lementioning
confidence: 99%